(untitled) (Raparin Journal of Humanities (RJH), 2021)
Logic is the measure and framework of thinking. Critical thinking means meticulous, organized, and purposeful thinking. Critical thinkers are not always critics. Critical thinking plays a role in every behavior, argumentation, and decision. These are accomplished through dialogue, explanation, and observation, in accordance with logical measures. Dialogue and thinking belong to logic. Logic is a means to organize the ways of human thinking. Critical thinking is a skill honed and improved by training and work, given the fact that most people are not born with an inherent skill of thinking critically, but that thinking is often restricted within a limited circle. This contradicts with critical thinking.